Intraorganizational Network Dynamics in Times of Ambiguity - Srivastava, Sameer B. (Organization Science, 2015)
Contrary to the assumption of relational inertia that is prevalent in much of the research on organizational change, I propose that intraorganizational networks are instead subject to transitory shifts when organizational change produces high levels of ambiguity for employees. I develop a theoretical account of how networks defined by formal, semiformal, and informal organizational structure change in response to heightened ambiguity. I argue that, when ambiguity increases, people will tend to (1) decrease communication with formal network ties that do not have a significant semiformal component, (2) increase communication with semiformal network ties that do not have a significant formal component, and (3) increase communication with informal network ties. Empirical support for these propositions comes from unique data—including 40 weeks of archived email metadata, the full roster of email distribution lists, personnel records, and qualitative interviews—that span the period before, during, and after an ambiguity-producing restructuring at a large information services firm. These findings contribute to research on organizational structure, organizational change, and social capital activation and also have implications for management practice.